Filamentous prophage capsid proteins contribute to superinfection exclusion and phage defence in Pseudomonas aeruginosa. (11th April 2022) - Wang, Weiquan; Li, Yangmei; Tang, Kaihao; Lin, Jianzhong; Gao, Xinyu; Guo, Yunxue; Wang, Xiaoxue
Summary: Filamentous prophages in Pseudomonas aeruginosa PAO1 are converted to superinfective phage virions during biofilm development. Superinfection exclusion is necessary for the development of resistance against superinfective phage virions in host cells. However, the molecular mechanisms underlying the exclusion of superinfective Pf phages are unknown. In this study, we found that filamentous prophage‐encoded structural proteins allow exclusion of superinfective Pf phages by interfering with type IV pilus (T4P) function. Specifically, the phage minor capsid protein pVII inhibits Pf phage adsorption by interacting with PilC and PilJ of T4P, and overproduction of pVII completely abrogates twitching motility. The minor capsid protein pIII provides partial superinfection exclusion and interacts with the PilJ and TolR/TolA proteins. Furthermore, pVII provides full host protection against infection by pilus‐dependent lytic phages, and pIII provides partial protection against infection by pilus‐independent lytic phages. Considering that filamentous prophages are common in clinical Pseudomonas isolates and their induction is often activated during biofilm formation, this study suggests the need to rethink the strategy of using lytic phages to treat P . aeruginosa biofilm‐related infections.